Pengaruh Tingkat Kecemasan Terhadap Kadar Gula Darah Pada Penderita Diabetes Melitus Tipe 2 - Bambang Fardiman; Saimi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
People with diabetes mellitus experience anxiety because the condition is considered a scary disease that has complex adverse effects on their anxiety levels. Uncontrolled diabetes often results in increased blood sugar levels. The chronic condition known as diabetes mellitus is caused by insufficient insulin production by the pancreas or inefficient use of insulin by the body. The purpose of this study was to determine how anxiety affects blood sugar levels in patients with diabetes mellitus at the Praya Health Center. This type of research is a quantitative study with a cross-sectional approach. The research sample of 140 respondents was determined by Random Sampling with the Zung Self-Rating Anxiety Scale (ZSAS) Questionnaire, an instrument used to measure a person's anxiety level. Based on the results of the study, the level of anxiety on blood sugar levels has a significant effect with a linier regeration statistical test obtained a coefficient value indicating that if the anxiety value increases by 1 unit, then the GDS will increase by 1.594 units, which means there is an influence and a significant value of 0.001 < (0.005) between the level of anxiety and blood sugar levels in patients with type 2 DM at the Praya Health Center